Reconceptualizing the Marriage Age Limit in Indonesia: Efforts to Strengthen Family Resilience in North Sumatra - Iwan; Fatimah; Betawi, Usman; Nasution, Muhammad Iqbal Hanafi (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
The issue of early marriage has become a polemic and still occurs frequently in Indonesian society. This paper considers the importance of limiting the age of marriage to prevent negative physical, social and emotional impacts on children. This paper abstracts how early marriage in Indonesia impacts family resilience. This type of research is field research, with a text analysis approach related to social issues to answer related factors that influence early marriage and how to improve family resilience. The author conducted research by interviewing five people, one of whom is the deputy head of the Religious Court, the other four are actors who play the role of parents in fulfilling the economical and social needs of children in low-income families, the impact of the increase in the marriage age limit on the rise in marriage dispensation applications at the Indonesian Religious Court, irregularities in marriage dispensation, the phenomenon of underage marriage, the practice of nikah sirri and its implications for marriage registration in Indonesia. The results show the need for better education, economic access, substantial law enforcement, and changes in social and cultural norms to address early marriage, concluding that limiting the age of marriage is vital to achieving family stability, happiness and well-being in Indonesia.